Bedtime versus morning use of antihypertensives for cardiovascular risk reduction (BedMed): protocol for a prospective, randomised, open-label, blinded end-point pragmatic trial - Garrison, Scott R; Kolber, Michael R; Allan, G Michael; Bakal, Jeffrey; Green, Lee; Singer, Alexander; Trueman, Darryl R; McAlister, Finlay A; Padwal, Raj S; Hill, Michael D; Manns, Braden; McGrail, Kimberlyn; et al. (BMJ open, 2022)
IntroductionSleep-time blood pressure correlates more strongly with adverse cardiovascular events than does daytime blood pressure. The BedMed trial evaluates whether bedtime antihypertensive administration, as compared with conventional morning use, reduces major adverse cardiovascular events.Methods and analysisDesignProspective randomised, open-label, blinded end-point trial.ParticipantsHypertensive primary care patients using blood pressure lowering medication and free from glaucoma.SettingCommunity primary care providers in 5 Canadian provinces (British Columbia, Alberta, Saskatchewan, Manitoba and Ontario) are mailing invitations to their eligible patients. Social media campaigns (Google, Facebook) are additionally running in the same provinces.InterventionConsenting participants are allocated via central randomisation to bedtime vs morning use of all antihypertensives.Follow-up(1) Telephone or email questionnaire at 1 week, 6 weeks, 6 months and every 6 months thereafter, and (2) accessing linked governmental healthcare databases tracking hospital and community medical services.Primary outcomeComposite of all-cause death, or hospitalisation for myocardial infarction/acute-coronary syndrome, stroke or congestive heart failure.Secondary outcomesEach primary outcome element on its own, all-cause hospitalisation or emergency department visit, long-term care admission, non-vertebral fracture, new glaucoma diagnosis, 18-month cognitive decline from baseline (via Short Blessed Test).Select other outcomesSelf-reported nocturia burden at 6 weeks and 6 months (no, minor or major burden), 1-year self-reported overall health score (EQ-5D-5L), self-reported falls, total cost of care (acute and community over study duration) and mean sleep-time systolic blood pressure after 6 months (via 24-hour monitor in a subset of 302 sequential participants).Primary outcome analysisCox proportional hazards survival analysis.Sample sizeThe trial will continue until a projected 254 primary outcome events have occurred.Current statusEnrolment ongoing (3227 randomised to date).Ethics and disseminationBedMed has ethics approval from six research ethics review boards and will publish results in a peer-reviewed journal.Trial registration numberNCT02990663.